The work life conflict of Malaysia Airlines call centre staff / Norlela Mahat - Mahat, Norlela (2014)
This paper presents the result of a study undertaken to understand the work life conflict of Malaysia Airlines call centre staff. Primary data was collected through questionnaire survey done by a sample of 139 staff of Malaysia Airlines call centre and analyzed. Work life conflict is an important issue for the call centre staff. The heavy reliance upon technology and uncertainty working hours, in particular are subject to the work life conflict. The finding of the study may have further implications for the industry and the society.